Peran Pendidikan Dayah Babussalam Al-Aziziyah Jeunieb Kabupaten Bireuen Dalam Menanggapi Problematika Keagamaan Masyarakat - Hanif Maulana; Zulfikar Ali Buto; Al-Husaini M. Daud (Institut Agama Islam Al-Aziziyah Samalanga, 2021)
Dayah is an educational institution that is taught in several fields of Islamic religious knowledge, such as monotheism, sufism, fiqh, interpretation, hadith, nahwu, sharaf, balaghah, and others to respond to the religious problems of society. So, the author examines how the role of dayah education responds to the religious problems of society. In this study the authors used a descriptive qualitative research type. The data collection technique is done by interview, observation, and documentation. As for the sources of data in this study are the leadership of the dayah, dayah teachers or administrators, and alumni of the dayah. The results showed that Dayah Babussalam Al-Aziziah Jeunieb has played a large role in the Jeunieb community and in general the Acehnese people in solving community religious problems, both from the fields of tauhid, tasawuf, and fiqh. Among the role of the dayah in society is the existence of majelis taklim, both the taklim majelis inside the dayah and outside the dayah, even the taklim majelis have arrived in Malaysia. And there are SD IT Islamic School, Assalam Al-Aziziyah Jeunieb Middle School, and Radio Yadara.